Comparative aspects of targeted sentinel lymph node mapping in veterinary and human medicine: opportunities for future research - Oblak, Michelle L.; Lu, Hui Yu; Ram, Ann S.; McKenna, Charly (Frontiers in Medicine, 2024)
There is a significant overlap in the genetic, metabolic and epigenetic alterations between human and companion animal cancers, including those of the oral cavity, breast, bladder, skin, lungs and pancreas. In many cancer types, the identification and removal of affected lymph nodes are essential for accurate cancer management, including treatment and prognosis. Historically, lymphadenectomy and subsequent radical resection based on regional anatomy, palpation and lymph node aspirates were considered sufficient; however, modern approaches with sentinel lymph node mapping (SLN) mapping have increased the accuracy of surgical decision-making. Preoperative and intraoperative SLN mapping techniques in veterinary patients parallel those used in human medicine. While many of these techniques are highly successful, the main challenges with current methodologies are their sensitivity and specificity for the presence of cancer, which can be overcome via precision medicine and targeted SLN mapping agents. Given the large population of dogs and cats with cancer, the crossover of knowledge between species can help to deepen our understanding of many of these cancers and can be useful in evaluating new drugs and/or therapies. In this review, we discuss SLN mapping techniques in veterinary medicine and the concept of precision medicine as it relates to targeted SLN mapping imaging agents. The large number of companion animals affected by cancer is an underutilized resource to bridge the translational gap and we aim to provide a reference for the use of dogs and cats as a comparative model for human SLN mapping.